INTERNALIZATION OF RELIGIOUS VALUES IN THE PROGRESSIVE EDUCATION PRACTICE AT PONDOK PESANTREN AL-AMANAH MODERN JUNWANGI SIDOARJO - Fahmi Ayatillah, M. Ishom; Fikry, Ahmad Jawahirun Ni'am; Abitolkha, Amir Maliki (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
Abstract: This study aims to analyze the process of internalizing religious values within the practice of progressive education at Pondok Pesantren Al-Amanah Modern Junwangi Sidoarjo, “especially through the Sanggar Tahfidz Entrepreneur program. The selection of this topic is based on the need to develop an Islamic education model that not only emphasizes spiritual dimensions but is also relevant to the demands of the 21st century. This research employs a qualitative field research approach using in-depth interviews, participatory observation, and documentation involving teachers, administrators, and students. The findings show that religious values such as sincerity, discipline, trustworthiness, responsibility, and patience are internalized through habituation, role modeling, and various tahfidz activities, including recitation submission, muroja’ah, mentoring, and strengthening Qur’anic etiquette. Meanwhile, progressivism principles are manifested through experiential learning (learning by doing), democratic participation, and reflective evaluation, as reflected in entrepreneurial activities ranging from production and digital marketing to business management. The integration of both aspects produces a holistic educational model in which religious values are not merely understood cognitively but are lived through real-life experiences that shape spiritual character, independence, creativity, and critical thinking skills. These findings affirm that pesantren education can adapt progressively without losing its religious identity. Keywords: entrepreneur; religious values; progressive education; progressivism; tahfidz